The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c6gc02586b
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial acidity in ligand-modified ruthenium nanoparticles boosts the hydrogenation of levulinic acid to gamma-valerolactone

Abstract: a Gamma-valerolactone (GVL), a versatile renewable compound listed among the top 10 most promising platform chemical by the US Department of Energy, is produced via hydrogenation of levulinic acid (LA). The traditional high-loading ruthenium-on-carbon catalyst (5 wt.% Ru) employed for this transformation suffers from low metal utilisation and poor resistance to deactivation due to the formation of RuO x species. Aiming at an improved catalyst design, we have prepared ruthenium nanoparticles modified with the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 68 publications
1
45
0
1
Order By: Relevance
“…Meijboom and colleagues obtained mesoporous supported dendrimers to immobilize Ru and Pt nanopartciels (<2 nm) and achieved 100 % selectivity towards GVL . Albani and coworkers used hexadecyl (2‐hydroxyethyl) dimethylammonium dihydrogen phosphate (HHDMA) to modify surface properties of titanium silicate support (entry#10 in Table ) . While experimental studies confirmed that HHDMA modified Ru catalyst (∼400 h −1 at 130 °C and 1.0 MPa) shows improved activity and stability compared with Ru/C catalyst (∼200 h −1 ), theoretical simulation suggested that H 2 dissociation shows lower activation barrier and is exothermic at the Ru‐HHDMA interface.…”
Section: Figurementioning
confidence: 99%
“…Meijboom and colleagues obtained mesoporous supported dendrimers to immobilize Ru and Pt nanopartciels (<2 nm) and achieved 100 % selectivity towards GVL . Albani and coworkers used hexadecyl (2‐hydroxyethyl) dimethylammonium dihydrogen phosphate (HHDMA) to modify surface properties of titanium silicate support (entry#10 in Table ) . While experimental studies confirmed that HHDMA modified Ru catalyst (∼400 h −1 at 130 °C and 1.0 MPa) shows improved activity and stability compared with Ru/C catalyst (∼200 h −1 ), theoretical simulation suggested that H 2 dissociation shows lower activation barrier and is exothermic at the Ru‐HHDMA interface.…”
Section: Figurementioning
confidence: 99%
“…Theover-hydrogenation and decomposition pathways are favored over Pd(111) compared to the formation of H 2 O 2 ( Figure S1). Other hydrogenation pathways,involving the protonation of adsorbed species due to interfacial acidity, [14] are likely not taking place if the low energy barriers for H 2 dissociation and OOH formation are considered. Notably,t he presence of the ligand increases the activation energy of the two side reactions.F urthermore,w ater formation attributed to O 2 dissociation is only feasible on the naked Pd surface,w hile it is thermodynamically impeded on the Pd(111)-HHDMA surface (Table S3).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In particular, lignocellulosic biomass, consisting of cellulose, hemicellulose, and lignin fractions, represents one of the most abundant and economical starting materials . The use of lignocellulosic biomass as a substrate for the efficient production of building blocks such as levulinic acid, γ‐valerolactone (GVL), 5‐hydroxymethylfuran (HMF), and dimethyl furan (DMF) has already been demonstrated on a laboratory scale . Among these, GVL, which is produced through the hydrodeoxygenation of lignocellulosic biomass, exhibits excellent solvent properties and is one of the main precursors in the synthesis of high‐value fine chemicals and polymers such as pentenoic acid, valeric acid, and α‐methylene‐γ‐valerolactone (MeGVL) .…”
Section: Introductionmentioning
confidence: 99%
“…[1] The use of lignocellulosic biomass as as ubstrate for the efficient production of building blocks such as levulinic acid, g-valerolactone (GVL),5 -hydroxymethylfuran (HMF), and dimethyl furan (DMF)h as already been demonstrated on al aboratorys cale. [4,[8][9][10][11][12][13] Among these, GVL, which is produced through the hydrodeoxygenation of lignocellulosic biomass,e xhibitse xcellent solventp roperties and is one of the main precursors in the synthesis of high-value fine chemicals and polymers such as pentenoic acid, valeric acid, and a-methylene-g-valerolactone (MeGVL). [1,4,14,15] In this regard, MeGVL is at ype of methacrylic monomerw itht he potential tos ubstitute the fossil-based methyl methacrylate (MMA),am onomer produced on al arge scale for the productiono fp oly(methyl methacrylate), the latter having numerous applicationsi nt he automotive, electronics, and medical sectors.…”
Section: Introductionmentioning
confidence: 99%